1999
DOI: 10.1053/eupc.1999.0056
|View full text |Cite
|
Sign up to set email alerts
|

Positive head-up tilt table test in patients with the long QT syndrome

Abstract: Our results suggest that patients with the LQTS are susceptible to neurally mediated syncope. Whether this susceptibility differs from control populations remains unresolved. From a clinical standpoint, neurocardiogenic syncope should be considered a diagnostic alternative in patients with LQTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…A recent [14] and the present study show that neurocardiogenic syncope can be induced in a majority of LQTS patients demonstrating that other mechanisms may be important. There was a slight tendency towards HUT being more often positive in LQTS than in patients without LQTS referred for HUT due to syncope (P < 0:10).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A recent [14] and the present study show that neurocardiogenic syncope can be induced in a majority of LQTS patients demonstrating that other mechanisms may be important. There was a slight tendency towards HUT being more often positive in LQTS than in patients without LQTS referred for HUT due to syncope (P < 0:10).…”
Section: Discussionmentioning
confidence: 88%
“…This is in common with vasovagal syncope, which is a frequently made erroneous diagnosis in LQTS patients, when the QT prolongation is overlooked. In a recent study all the six patients investigated with a head-up tilttable test (HUT) had a positive test of mixed response [14] . No genetic classification was made in that study.…”
Section: Introductionmentioning
confidence: 99%
“…The syncope was subsequently demonstrated to be neurocardiogenic syncope. Abnormal tilt table-table tracing have been linked to prolonged QT syndromes [6] which suggests a neurocardiogenic reflex may aggravate an underlying electrical abnormality should it be present.…”
Section: Discussionmentioning
confidence: 99%
“…19 In fact, small studies have shown that patients with LQTS are prone to VVS. 20,21 Furthermore, in all large series reporting on consecutive patients with BrS, the long-term risk for spontaneous VF for patients initially presenting with syncope is intermediate: lower than that for patients presenting with cardiac arrest but significantly higher than that for initially asymptomatic patients. 22,23 This consistent finding suggests that the BrS patient-group presenting with syncope actually includes 2 different patient populations, one presenting with arrhythmic syncope and malignant course during follow-up and one with vagal syncope and benign prognosis.…”
Section: Symptomsmentioning
confidence: 97%